MODERN PRESCHOOL EDUCATION: EUROPEAN EXPERIENCE - Kozak, Luydmila (Educological discourse, 2017)
The article substantiates the expediency of studying European experience in solving modern problems of preschool education in Ukraine. The experience of the organization of preschool education in France, Great Britain, Germany has been analyzed. It is shown that the systems of pre-school education in these countries have their own peculiarities and their own promising experience. The main tasks of the French «Ecole maternelle» are the development of social, communicative and aesthetic skills, creating a comfortable environment for the development of the child's personality. All institutes of pre-school education in Germany are called to promote the development of the child as a responsible and independent member of society. Education is organized in such a way as to support and supplement the upbringing of the child in the family, to provide the best opportunities for its development and education. The content and methods of educational work with children in the "nursery schools" of Great Britain are determined mainly in the context of the ideas of "free education". It has been established that common for preschool establishments of European countries is a special attention to the creation of a developing environment and the organization of various activities that contribute to the overall development of the child and its preparation for school education. Preparation of teaching staff for work in pre-school institutions is carried out in each country according to its own system of vocational training (courses, secondary specialized institutions, institutes, universities, higher schools). The ideas that can be applied in the development of preschool education in Ukraine are outlined.